Stakeholders' involvement in KMS implementation for Thai ceramic SMEs: A conceptual framework - Nupap S. (2014)
Recently, over 80 percent of ceramic SMEs in Lampang, known as the biggest source of ceramic production in Thailand have been closed down rapidly due to several reasons such as the difficulties to find funds for sustainment and facing intensive competition in the global market. To overcome this situation, we propose a Knowledge Management System (KMS) framework based on Intellectual Capital (IC) theory. This framework is based on the identification of the various stakeholders of the enterprise and their roles in creating the knowledge. To improve performance of SMEs, we propose to develop four perspectives: Business Plan, Business Process Reengineering (BPR), Enterprise Resource Planning (ERP), and New Product Development (NPD) using the Joint Application Design (JAD). © 2012 IFAC.